Search for Randall-Sundrum gravitons in the dielectron and diphoton final states with 5.4fb-1 of data from pp̄ collisions at √s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; et al. (My University, 2010)
Using 5.4fb-1 of integrated luminosity from pp̄ collisions at √s=1.96 TeV collected by the D0 detector at the Fermilab Tevatron Collider, we search for decays of the lightest Kaluza-Klein mode of the graviton in the Randall-Sundrum model to ee and γγ. We set 95 C.L. lower limits on the mass of the lightest graviton between 560 and 1050 GeV for values of the coupling k/M̄Pl between 0.01 and 0.1. © 2010 The American Physical Society.